Sinularin induces oxidative stress‐mediated G2/M arrest and apoptosis in oral cancer cells - Chang, Yung‐Ting; Wu, Chang‐Yi; Tang, Jen‐Yang; Huang, Chiung‐Yao; Liaw, Chih‐Chuang; Wu, Shih‐Hsiung; Sheu, Jyh‐Horng; Chang, Hsueh‐Wei (Environmental toxicology, 2017)
Soft corals‐derived natural product, sinularin, was antiproliferative against some cancers but its effect and detailed mechanism on oral cancer cells remain unclear. The subject of this study is to examine the antioral cancer effects and underlying detailed mechanisms in terms of cell viability, oxidative stress, cell cycle analysis, and apoptosis analyses. In MTS assay, sinularin dose‐responsively decreased cell viability of three oral cancer cells (Ca9‐22, HSC‐3, and CAL 27) but only little damage to oral normal cells (HGF‐1). This cell killing effect was rescued by the antioxidant N‐acetylcysteine (NAC) pretreatment. Abnormal cell morphology and induction of reactive oxygen species (ROS) were found in sinularin‐treated oral cancer Ca9‐22 cells, however, NAC pretreatment also recovered these changes. Sinularin arrested the Ca9‐22 cells at G2/M phase and dysregulated the G2/M regulatory proteins such as cdc2 and cyclin B1. Sinularin dose‐responsively induced apoptosis on Ca9‐22 cells in terms of flow cytometry (annexin V and pancaspase analyses) and western blotting (caspases 3, 8, 9) and poly (ADP‐ribose) polymerase (PARP). These apoptotic changes of sinularin‐treated Ca9‐22 cells were rescued by NAC pretreatment. Taken together, sinularin induces oxidative stress‐mediated antiproliferation, G2/M arrest, and apoptosis against oral cancer cells and may be a potential marine drug for antioral cancer therapy.